Performance measurement of value management (VM) for the Malaysian construction industry - Mohsen Torabi, 1985-; Abdul Kadir Marsono; Fakulti Kejuruteraan Awam (2012)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2012